Audit in the European countries - Ponomarenko, Ruslana (My University, 2014)
Today, the internal and external audit in all foreign countries has certain peculiarities. Through the study of foreign experience in the sphere of audit it can be used to improve the effectiveness of the Ukrainian independent audit. The fact that many problems in the auditors' activity are related to drawbacks and imperfections in the normative basis regulating the audit activities as well as in the methodology of execution of audit also points out at the necessity to study the regulative requirements of audit.
Keywords: european countries; experience; audit; європейські країни; досвід